Resistance, aerobic and combination training on vascular function in overweight and obese adults - Ho, Suleen; Radavelli-Bagatini, Simone; Dhaliwal, Satvinder; Hills, A.; Pal, Sebely (Le Jacq Communications Inc, 2012)
The authors investigated the effects of moderate-intensity resistance, aerobic, or combined exercise on blood pressure and arterial stiffness in overweight and obese individuals compared with no exercise. Participants were randomized to 4 groups: control, aerobic, resistance, and combination. Assessments were made at baseline, week 8, and week 12. In participant-designated responders, those in the intervention groups who had improved levels of systolic blood pressure (SBP) or augmentation index (AI), we observed a significant decrease of SBP in aerobic (-4%, P=.027), resistance (-5.1%, P=.04), and combination groups (-6.3%, P=.000) at week 8 and in the combination group (-6.3%, P=.005) at week 12, compared with baseline. AI was significantly lower at week 12 in the aerobic (-12%, P=.047), resistance (-9.5%, P=.036), and combination (-12.7%, P=.003) groups compared with baseline, as well as in the combination group (-10.7%, P=.047) compared with the control group. We did not observe significant changes in SBP, DBP, or AI between the interventions when assessing the entire cohort, although there were significant improvements in a subgroup of responders. Thus, some but not all overweight and obese individuals can improve blood pressure and arterial stiffness by participating in regular combination exercise, decreasing the risk of developing cardiovascular disease.